Pendampingan Kegiatan Menghafal Al-Qur’an Peserta Didik menggunakan Metode Tikrar Berbantuan Audio Speaker - Elfi Rahmi; Martin Kustati; Gusmirawati Gusmirawati (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
The partner for this mentoring activity is the YATI Kamang Mudik Islamic Boarding School, which is facing a severe imbalance in the amount of Quran memorization among students. Differences in memory capacity mean that some participants memorize faster, while others fall far behind. This issue not only affects memorization achievement but also impacts motivation, self-confidence, and the overall effectiveness of the tahfiz learning process. Therefore, immediate intervention is needed to introduce learning methods that can equalize students' memorization abilities. One of the proposed efforts is the implementation of the tikrar method, which is an intensive and structured memorization repetition technique. The mentoring activity was conducted using the Participatory Action Research (PAR) approach, directly involving students thru three main stages: (1) planning activities based on identifying partner problems; (2) implementing the tikrar method of mentoring thru repeated memorization practice and using audio speakers as an aid; and (3) evaluation to assess memorization progress and students' responses to the application of the method. The mentoring results showed that the tikrar method, applied consistently, was able to improve the quality and quantity of students' memorization. The use of audio speakers helps clarify pronunciation, strengthen auditory memory, and make it easier for participants to follow along independently.